UK Government offers initiatives and assurances. Issue 5 (May 2019) - Unknown
Abstract : A number of UK government agencies used the recent CyberUK 2019 conference, hosted by the National Cyber Security Centre (NCSC), to clarify their positions on cyber security and offer assurances to businesses.